Increased MFG‐E8 at neuromuscular junctions is an exacerbating factor for sarcopenia‐associated denervation. Issue 1 (24th December 2021) - Ikemoto‐Uezumi, Madoka; Zhou, Heying; Kurosawa, Tamaki; Yoshimoto, Yuki; Toyoda, Masashi; Kanazawa, Nobuo; Nakazawa, Tatsu; Morita, Mitsuhiro; Tsuchida, Kunihiro; Uezumi, Akiyoshi
Abstract: Sarcopenia is an important health problem associated with adverse outcomes. Although the etiology of sarcopenia remains poorly understood, factors apart from muscle fibers, including humoral factors, might be involved. Here, we used cytokine antibody arrays to identify humoral factors involved in sarcopenia and found a significant increase in levels of milk fat globule epidermal growth factor 8 (MFG‐E8) in skeletal muscle of aged mice, compared with young mice. We found that the increase in MFG‐E8 protein at arterial walls and neuromuscular junctions (NMJs) in muscles of aged mice. High levels of MFG‐E8 at NMJs and an age‐related increase in arterial MFG‐E8 have also been identified in human skeletal muscle. In NMJs, MFG‐E8 is localized on the surface of terminal Schwann cells, which are important accessory cells for the maintenance of NMJs. We found that increased MFG‐E8 at NMJs precedes age‐related denervation and is more prominent in sarcopenia‐susceptible fast‐twitch than in sarcopenia‐resistant slow‐twitch muscle. Comparison between fast and slow muscles further revealed that arterial MFG‐E8 can be uncoupled from sarcopenic phenotype. A genetic deficiency in MFG‐E8 attenuated age‐related denervation of NMJs and muscle weakness, providing evidence of a pathogenic role of increased MFG‐E8. Thus, our study revealed a mechanism by which increased MFG‐E8 at NMJs leads to age‐related NMJ degeneration and suggests that targeting MFG‐E8 could be a promising therapeutic approach to prevent sarcopenia. Abstract : Milk fat globule epidermal growth factor 8 (MFG‐E8) levels at neuromuscular junctions (NMJs) increase during aging. A genetic deficiency in MFG‐E8 attenuated age‐related denervation of NMJs and muscle weakness, providing evidence of a pathogenic role of increased MFG‐E8. This study revealed a previously unrecognized mechanism of age‐related NMJ denervation associated with sarcopenia.